The Influence of Foreign Debt and Foreign Direct Investment on Economic Growth in Indonesia - Siti Fatimatu Zahro; Sutrisno Sutrisno; Ilham Abu; Ratna Fitri Astuti (Journal of Economic Education and Entrepreneurship Studies, 2025)
Economic growth remains a primary concern for the government. To stimulate economic growth, the government has implemented foreign debt and foreign direct investment policies. The objective of this research is to examine the influence of foreign debt and foreign direct investment on Indonesia's economic growth. This research employs explanatory research with a quantitative approach, utilizing population and sample data consisting of foreign debt, foreign direct investment, and economic growth from 2013 to 2023. The data analysis techniques include classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, 1 and autocorrelation test), multiple linear regression, hypothesis testing (t-test and F-test), and 2 the coefficient of determination test, using EViews 12 to analyze the data.